Biochar - reversing the flow of carbon - Trevor, Richards (UTAR Agriculture Science Journal, 2015)
This is a story about biochar... charcoal by another name but with a much larger story. It is a story that has rapidly evolved in the last 10 years and will expand into the future but it starts a few thousand years ago. (This article includes terms that may not be familiar or require definition. Selected terms and references are listed at the bottom of each page with links to Wikipedia and other sources.)